Bioprocesses characterization of 2-L sonobioreactor - Azilah, Ajit; Wan Siti Atikah, Wan Omar; Ahmad Ziad, Sulaiman (Elsevier Ltd, 2018)
Bioprocess characterizations are commonly evaluated to justify the use, setting alteration and future scaling-up. This paper discussed on some bioprocess characterization of 2-L sonobioreactor against the standard bioreactor (control). The objective of this study was to evaluate whether the additional and adjustment of a standard bioreactor into a sonobioreactor had a differentbioprocesses characters. The bioreactor was set at four settings, 1) control, 2) control with flow rate, 3) flow rate with 10% duty cycle and 4) flow rate with 40% duty cycle. Accordingly, four simple characterizations were measured, power number, mixing time, response time, and volumetric mass coefficient. The results showed most of the characterizations were similar except for the mixing time. The control was found significantly faster than other settings at 10 s by a conductivity method. As a conclusion,findings explained the sonobioreactor settings affected the mixing time due to the use of flow rate and sonication.